1980
DOI: 10.3382/ps.0592225
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin A Deficiency on Some Postmortem Parameters of Avian Muscle

Abstract: The effect of the dietary status of vitamin A on carbohydrate metabolism, postmortem isometric tension development, and shear resistance of Pectoralis major muscle was studied. Depletion studies conducted over a 5-week period indicated a definite influence of vitamin A deficiency on muscle carbohydrate metabolism. Mild hypovitaminosis A induced an increase in glycogen deposition, whereas severe deficiency led to a reduction of these elevated stores. Vitamin A deficiency did not affect the ability of P. major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…However, very limited research has been performed to investigate the effects of VA on carbohydrate and protein metabolism in the skeletal muscle. In avian species, VA deficiency depletes the glycogen content in the pectoralis major muscle [ 183 ]. On the other hand, RA treatment of mouse myoblast C2C12 cells leads to increased glucose uptake, possibly through the activation of AMP-activated protein kinase [ 184 ].…”
Section: Va and Metabolism In The Skeletal Musclementioning
confidence: 99%
“…However, very limited research has been performed to investigate the effects of VA on carbohydrate and protein metabolism in the skeletal muscle. In avian species, VA deficiency depletes the glycogen content in the pectoralis major muscle [ 183 ]. On the other hand, RA treatment of mouse myoblast C2C12 cells leads to increased glucose uptake, possibly through the activation of AMP-activated protein kinase [ 184 ].…”
Section: Va and Metabolism In The Skeletal Musclementioning
confidence: 99%
“… Sundeen et al (1980) , when evaluating diets that are poor in vitamin A, observed that birds with mild hypovitaminosis A had increased glycogen deposition in their pectoralis major muscle, and that, in cases of severe vitamin deficiency, these stocks were reduced. In cases when, after a period of deficiency, birds received diets adequately supplemented with vitamin A, the muscular glycogen content was equal to that of birds adequately supplemented.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sundeen et al (1980) , vitamin A influences hepatic carbohydrate metabolism, where hepatic glycogen deposition is largely reduced in cases of hypovitaminosis A. This vitamin, as well as retinol, has a broad role in macronutrient homeostasis as an essential micronutrient and an indispensable lipophilic for the maintenance of the animals’ general health, since it seems to act on the metabolism of carbohydrates, lipids, and proteins in the liver, pancreas, skeletal muscle, and adipose tissue, consequently playing a role in the metabolism of glucose and fatty acids ( Chen and Chen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estudando o efeito da vitamina A no metabolismo dos carboidratos e sua influência na musculatura das aves, SUNDEEN et al (1980) registraram que o fornecimento de rações deficientes em vitamina A para as aves, afetaram a integridade estrutural do tecido muscular, resultando músculos mais rijos, expressos pelo maior valor de resistência ao corte.…”
Section: Introductionunclassified